Selection of astrophysical/astronomical/solar sites at the Argentina East Andes range taking into account atmospheric components. Issue 12 (15th June 2016) - Piacentini, R.D.; García, B.; Micheletti, M.I.; Salum, G.; Freire, M.; Maya, J.; Mancilla, A.; Crinó, E.; Mandat, D.; Pech, M.; Bulik, T.
Abstract: In the present work we analyze sites in the Argentinian high Andes mountains as possible places for astrophysical/astronomical/solar observatories. They are located at: San Antonio de los Cobres (SAC) and El Leoncito/CASLEO region: sites 1 and 2. We consider the following atmospheric components that affect, in different and specific wavelength ranges, the detection of photons of astronomical/astrophysical/solar origin: ozone, microscopic particles, precipitable water and clouds. We also determined the atmospheric radiative transmittance in a day near the summer solstice at noon, in order to confirm the clearness of the sky in the proposed sites at SAC and El Leoncito. Consequently, all the collected and analyzed data in the present work, indicate that the proposed sites are very promising to host astrophysical/astronomical/solar observatories. Some atmospheric components, like aerosols, play a significant role in the attenuation of light (Cherencov and/or fluorescence) detected in cosmic rays (particles or gamma photons) astrophysical observatories, while others, like ozone have to be considered in astronomical/solar light detection.